2017
DOI: 10.1021/acs.jpcb.7b10170
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Level Understanding of Sodium Dodecyl Sulfate (SDS) Induced Sol–Gel Transition of Pluronic F127 Using Fisetin as a Fluorescent Molecular Probe

Abstract: The thermoreversible sol-gel transition of pluronic F127 is markedly altered even with addition of submicellar concentration of sodium dodecyl sulfate (SDS) surfactant. Multiple fluorescence parameters like fluorescence intensity, fluorescence anisotropy and fluorescence lifetime of both the prototropic forms (anion (A*) and phototautomer FT*) of the photoprototropic fluorescent probe fisetin has been efficiently used to understand the molecular level properties like polarity and microviscosity of the PF127-SD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 38 publications
0
16
1
Order By: Relevance
“…It is demonstrated that the calculated dielectric constants for polymeric nanocarriers are very close to literature values for these polymers, which validates NI 3 as an adequate fluorescent dye to probe local polarity in polymeric nanoparticles. However, the calculated apparent polarity for surfactant micelles is lower than those determined in other works using solvatochromic dyes [34,35]. These differences may be attributed to conformational effects due to the smaller size of micelles compared to polymeric NPs, or to a localization of 3 within the micelle hydrophobic center.…”
Section: Resultscontrasting
confidence: 70%
“…It is demonstrated that the calculated dielectric constants for polymeric nanocarriers are very close to literature values for these polymers, which validates NI 3 as an adequate fluorescent dye to probe local polarity in polymeric nanoparticles. However, the calculated apparent polarity for surfactant micelles is lower than those determined in other works using solvatochromic dyes [34,35]. These differences may be attributed to conformational effects due to the smaller size of micelles compared to polymeric NPs, or to a localization of 3 within the micelle hydrophobic center.…”
Section: Resultscontrasting
confidence: 70%
“…In our previous study we have observed that, with increase in SDS concentration, hydrophobicity of the PF127 medium increases. This decrease in medium hydrophobicity leads to decrease the transition temperature . A molecular level understanding on the interaction of higher concentration of surfactants on the transition temperature of PF127 copolymer requires a detailed analysis of the fluorescence intensity and lifetime data of both the prototropic forms of fisetin which will be discussed further.…”
Section: Resultsmentioning
confidence: 99%
“…The longer lifetime value decreases with increase in temperature from sol‐gel phase of PF127, PF127+TW20 and PF127+CTAB whereas it almost remains constant for PF127+SDS. In our previous study, we have reported that the shorter lifetime value originates from core‐corona domain whereas the longer lifetime value originates from aqueous‐corona domain, so the increase in lifetime value of shorter component from nonionic to ionic surfactant indicates the increase in microviscosity at the core‐corona domain of PF127 in presence of surfactants. The variation in the corresponding relative amplitudes of both the components is represented in Figure S5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various additives like salts, ionic liquids, nonelectrolytes, nanoparticles, surfactants, alcohols, carbohydrates, , and polymers , were reported to change the CMT of different Pluronic systems. ,,, Among these materials, saccharide molecules, which play several important roles in various biological processes, exhibit a significant effect on the aggregation behavior of Pluronics. Kim et al reported lowering of the lower critical solution temperature (LCST) of thermoresponsive polymers in the presence of different saccharides based on the cloud point measurements .…”
Section: Introductionmentioning
confidence: 99%